The Relationship Between Mosquito Breeding Sites and Waste Management with the Incidence of Dengue Hemorrhagic Fever (DHF) in Citimun Village, Cimalaka District in 2023 - Pratami, Widiani; Sonjati, Evi (Jurnal Ilmu Kesehatan, 2024)
Dengue is a viral disease transmitted by Aedes mosquitoes. There are four types of dengue virus (DENV-1, DENV-2, DENV-3. DENV-4), and infection with one type provides lifelong immunity against only that type. One of the factors that can influence the increase in morbidity and death rates due to dengue disease is poor community behavior related to poor environmental sanitation. This study aims to determine the relationship between mosquito breeding sites and waste management with the incidence of Dengue Hemorrhagic Fever (DHF) in the Citimun Village Area. The type of research used is quantitative research that is descriptive analytic with a cross sectional approach. The population in this study is the population of Citimun Village which amounts to 5,274 households, with a sample number of 100 families determined by the slovin formula. The data analysis used was univariate and bivariate data analysis using the Chi-Square test.The results showed that there was a relationship between mosquito breeding sites and dengue incidence with a p-value of 0.001, and there was a relationship between waste management and dengue incidence with a p-value of 0.006. It is hoped that village officials and epidemiological surveillance officers at puskesmas can provide counseling to the community so that the community can maintain good environmental cleanliness and to avoid disease.